The best of sewing machine fun for kids - Smith, Nancy, 1943 Oct. 17-; Milligan, Lynda, 1951- (Denver, CO : Possibilities, 2003)
Offering a delightful introduction to the world of sewing for children ages seven and older, The Best of Sewing Machine Fun for Kids offers clear, colorful directions to help kids have fun as they develop skills that will last a lifetime. Thirteen kid-friendly projects easily teach children how to sew. As kids work their way through the book, each project builds on skills they have already learned. Easy-to-follow instructions and safety precautions start with sewing basics, allowing children to learn at their own pace.
Keywords: Machine sewing -- Juvenile literature; Handicraft -- Juvenile literature; Sewing; Handicraft